Pengaruh Model Pembelajaran Kooperatif Tipe Gallery Walk Terhadap Minat Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XII IPS Di SMA Negeri 8 Kota Jambi - Amelia Friska (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of the application of the gallery walk cooperative learningmethod on students' learning interest in economics class XII IPS at SMA Negeri 8 Jambi City. This type ofresearch uses a quantitative approach. Meanwhile, the techniques in this study used correlation techniques todetermine the direction and data collection to be carried out in the study. The results showed that the gallerywalk cooperative learning model has a significant influence on learning interest. Thus, there is a positiveinfluence of the Gallery Walk type of cooperative learning model on students' interest in economics subjects inclass XII IPS at SMA Negeri 8 Jambi City.